Effects of Lutein/Zeaxanthin Supplementation on the Cognitive Function of Community Dwelling Older Adults: A Randomized, Double-Masked, Placebo-Controlled Trial - Hammond, Billy R.; Miller, L. Stephen; Bello, Medina O.; Lindbergh, Cutter A.; Mewborn, Catherine; Renzi-Hammond, Lisa M. (Frontiers in Aging Neuroscience, 2017)
Background. High levels of xanthophyll carotenoids lutein (L) and zeaxanthin (Z) in the central nervous system have been previously correlated with improved cognitive function in community-dwelling older adults. In this study, we tested the effects of supplementing L and Z on older men and women with a range of baseline cognitive abilities. Objective. The purpose of this study was to determine whether or not supplementation with L+Z could improve cognitive function in community-dwelling, older adults. Design. Double-masked, randomized, placebo-controlled trial. A total of 62 older adults were randomized into groups receiving either 12 mg L+Z or a visually identical placebo. Data from 51 participants (M = 73.7 years) were available for analysis. Retinal L+Z levels (macular pigment optical density, MPOD) were measured psychophysically using heterochromatic flicker photometry as a biomarker of cortical L+Z levels. Cognitive function was measured using the CNS Vital Signs computerized test platform. Results. Participants receiving the active L+Z supplement had statistically significant increases in MPOD (p < 0.03) and improvements in complex attention (p < 0.02) and cognitive flexibility domains (p < 0.04), relative to participants taking the placebo. A trend was also seen for the executive function domain (p = 0.073). In male participants only, supplementation yielded improved composite memory (p = 0.04). Conclusions. Supplementation with L+Z improved cognitive function in community-dwelling, older men and women.